2017
DOI: 10.1680/jmuen.16.00016
|View full text |Cite
|
Sign up to set email alerts
|

Implementing value engineering study for temporary facilities

Abstract: Value engineering (VE) is a technique for reducing costs while keeping the required function, and improves performance and quality. It can be applied in many areas. In construction projects, VE is typically carried out for the project itself, but not for mobilisation and temporary facilities. For large and remote construction projects, the cost of mobilisation and temporary facilities is considerably high. So, a VE study could lead to a significant saving in the construction costs. This paper provides evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Thompson, et al, (2009) applied VE, considering site complexities to select a suitable type of embankment stabilization system. VE was also applied for identifying suitable cost-effective temporary facilities such as selecting the sources of electricity supply for the mobility phases of the project (Trigunarsyah and Hamzeh, 2017).…”
Section: Ve During Construction Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thompson, et al, (2009) applied VE, considering site complexities to select a suitable type of embankment stabilization system. VE was also applied for identifying suitable cost-effective temporary facilities such as selecting the sources of electricity supply for the mobility phases of the project (Trigunarsyah and Hamzeh, 2017).…”
Section: Ve During Construction Stagesmentioning
confidence: 99%
“…The VE practices for construction were found applied for various buildings (Lee, 2018;Berawi, et al, 2021), and infrastructure projects such as highways (Atabay and Galipogullari, 2013;Kim, et al, 2016;Mousakhani, et al, 2017), bridges (Basha and Gab-Allah, 1991;Tang and Bittner, 2014), power stations (Trigunarsyah and Hamzeh, 2017;Li, et al, 2019) and other utility projects (Cuimei and Suiqing, 2008). However, their application specific to the construction of metro rail infrastructure projects are seldom targeted.…”
Section: Ve In Post-construction Stagementioning
confidence: 99%
“…The paper by Trigunarsyah and Hamzeh (2017) focuses on the utilisation of value engineering technique to study the mobilisation and temporary facilities in construction projects and it has been evidently shown that it could lead to significant costs reduction without compromising the quality and functionality. Delaney et al (2017) conducted an extensive user experience surveys on a typical off-road shared-use route in Bristol, UK with an aim to contribute to the enhancement of design and management of shared-use paths.…”
mentioning
confidence: 99%